2020
DOI: 10.24018/ejmed.2020.2.3.267
|View full text |Cite
|
Sign up to set email alerts
|

A Study On Comparison Of Pain Score Between Upper Limb And Lower Limb Fractures

Abstract: Introduction: Pain is the most common chief complaint of patients presenting to Emergency Department (ED). Pain is not simply a signal for tissue injury, but also a signal to seek repair and recuperation. The aim of this study was to determine whether upper limb (UL) or lower limb (LL) fracture has more pain and to evaluate the association between types of fracture (UL vs LL) with adequacy of pain relief. Methodology: A study was conducted from July to October 2005 in ED, Hospital Universiti Sains Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…This study showed that majority and all of the subjects had high level of bodily pain before and after one week of fixation surgery. This observation is similar to the conclusion of the research made by Baharuddin et al (30) who pointed out that above two thirds of patients with lower extremity fracture with fixation surgery had poor bodily pain dimension. Also, Sluys et al (31) mentioned that majority of patient with upper extremity fracture with fixation surgery had poor bodily pain.…”
Section: Resultssupporting
confidence: 91%
“…This study showed that majority and all of the subjects had high level of bodily pain before and after one week of fixation surgery. This observation is similar to the conclusion of the research made by Baharuddin et al (30) who pointed out that above two thirds of patients with lower extremity fracture with fixation surgery had poor bodily pain dimension. Also, Sluys et al (31) mentioned that majority of patient with upper extremity fracture with fixation surgery had poor bodily pain.…”
Section: Resultssupporting
confidence: 91%
“…It is well established that ISE is an essential component of orthopaedic rehabilitation. ISE is a simple and safe start to recovery as it strengthens muscle power, prevents muscle atrophy and joint stiffness, and reduces musculoskeletal pain, especially in the area of postsurgical fracture (Baharuddin et al, 2020). Hence, ISE may be prescribed as a nonpharmacological method to manage postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that ISE is an essential component of orthopaedic rehabilitation. ISE is a simple and safe start to recovery as it strengthens muscle power, prevents muscle atrophy and joint stiffness, and reduces musculoskeletal pain, especially in the area of postsurgical fracture (Baharuddin et al, 2020). Hence, ISE may be The benefits of isometric strengthening exercises (ISEs) are compromised when patient teaching on ISEs is delayed and/or ineffectively delivered due to healthcare resources constraint, especially when health resources are stretched, as occurred during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%